Illness Perceptions of COVID-19 in Europe: Predictors, Impacts and Temporal Evolution - Dias Neto, David; Nunes da Silva, Ana; Roberto, Magda Sofia; Lubenko, Jelena; Constantinou, Marios; Nicolaou, Christiana; Lamnisos, Demetris; Papacostas, Savvas; Höfer, Stefan; Presti, Giovambattista; Squatrito, Valeria; Vasiliou, Vasilis S.; et al. (Frontiers in Psychology, 2021)
Objective. Illness perceptions (IP) are important predictors of emotional and behavioral responses in many diseases. The current study aims to investigate the COVID-19-related IP throughout Europe. The specific goals are to understand the temporal development, identify predictors (within demographics and contact with COVID-19) and examine the impacts of IP on perceived stress and preventive behaviors. Methods. This was a time-series-cross-section study of 7032 participants from 16 European countries using multilevel modeling from April to June 2020. IP were measured with the Brief Illness Perception Questionnaire. Temporal patterns were observed considering the date of participation and the date recoded to account the epidemiological evolution of each country. The outcomes considered were perceived stress and COVID-19 preventive behaviors. Results. There were significant trends, over time, for several IP, suggesting a small decrease in negativity in the perception of COVID-19 in the community. Age, gender, and education level related to some, but not all, IP. Considering the self-regulation model, perceptions consistently predicted general stress and were less consistently related to preventive behaviors. Country showed no effect in the predictive model, suggesting that national differences may have little relevance for IP, in this context. Conclusion. The present study provides a comprehensive picture of COVID-19 IP in Europe in an early stage of the pandemic. The results shed light on the process of IP formation with implications for health-related outcomes and their evolution.